Understanding Nepal’s Geopolitical Dynamics: Connected History Disconnected Future - Bhatta, Chandra Dev (Journal of Foreign Affairs, 2022)
The debate on geopolitics has gained momentum at various layers of society in recent years. Yet, there is paucity in clarity as to what geopolitics entails and how Nepal has become geopolitically important. There are, however, multiple opinions, where the tendency has been to project geography as the main tenet of geopolitics. This may partially be true given the changes brought about by the new technology-driven political economy. Likewise, there is a tendency to associate every success and failure in the domestic politics/development with geopolitics, while other undercurrents are not taken into consideration even though they might have implications for keeping the society and state together in the long-term. What is still important for the states like Nepal is the role of powerful countries both in the neighborhood and beyond. Geopolitics certainly is not new, but its manifestations may differ, and this article looks into them and their possible consequences for Nepal. In this regard shall also carefully considers how foreign policy should be articulated when geopolitics is entrenched. The article largely builds on an analytical approach based on certain facts/events to understand and explain the geopolitical underpinnings.